Non-invasive global myocardial work index as a new surrogate of ventricular-arterial coupling in hypertensive patients with preserved left ventricular ejection fraction - Duan, Qin; Tao, Hongmei; Dong, Qian; Liao, Kangla; Yang, Yunjing; Cheng, Xiaocheng; Ge, Ping (Frontiers in Cardiovascular Medicine, 2022)
Objective: As a new method of left ventricular-arterial coupling (VAC), non-invasive myocardial work index (MWI) may provide more useful information than the classical methods of arterial elastance/left ventricular elastance index (Ea/Ees). This research aims investigating if MWI might be better associated with hypertension-mediated organ damage (HMOD) and diastolic dysfunction than Ea/Ees in hypertension. Methods: We prospectively enrolled 104 hypertensives and 69 normotensives. All subjects had speckle-tracking echocardiography for myocardial work, conventional echocardiography and brachial-ankle pulse wave velocity (baPWV) measurements. Global work index (GWI) is a myocardial work component. Correlation between GWI and HMOD, as well as diastolic dysfunction, were analyzed. The receiver operating characteristic (ROC) curve was utilized for evaluating the GWI predicting efficacy. Results: GWI was significantly higher in hypertensives than in normotensives (2021.69±348.02 mmHg% vs. 1757.45±225.86 mmHg%, respectively, P <0.001). Higher GWI was a risk factor on its own for increased baPWV, pulse pressure (PP), echocardiographic left ventricular hypertrophy (LVH), and left atrial volume index (LAVI) (P =0.030, P <0.001, P =0.018 P =0.031 respectively), taking into account the sex, age, mean arterial pressure, body mass index (BMI) and antihypertensive therapy. However, no considerable associations were found between Ea/Ees and HMOD parameters and the diastolic dysfunction markers. The GWI area under the ROC curve for increased PP and baPWV, echocardiographic LVH, and increased LAVI were 0.799, 0.770, 0.674, and 0.679, respectively (P < 0.05). Conclusions: GWI but not traditionally echocardiographic-derived Ea/Ees of VAC is independently related to HMOD and diastolic impairment in hypertensives with preserved left ventricular ejection fraction. GWI may be a potential marker for evaluating the VAC in hypertension.